The concept «traditional Chinese medicine» in modern media texts about COVID-19 treatment in Russian and Chinese languages - Chen, Kuo; Karabulatova, Irina S. (Journal of the Belarusian State University. Journalism, 2024)
Traditional Chinese medicine as a unique ethno-cultural theoretical and practical valeological system has extensive experience in the prevention and treatment of diseases based on the normalisation of alternative neuro-linguopsycho-physiological communication between a person and his body. The author of the article analyses the content of messages from modern Russian- and Chinese-language speakers about the use of traditional Chinese medicine in the treatment of the COVID-19, and also offers an assessment of the effectiveness of traditional Chinese medicine during the COVID-19 pandemic in modern Russian- and Chinese-language media messages. The purpose of the work is to analytically examine media messages about traditional Chinese medicine in Russia and China from the perspective of «translating» signs of nonverbal-paraverbal means of communication between the body and a person in the interpretative philosophical ideas of traditional Chinese medicine.